Clinical pharmacists' intervention on pain management in cancer patients (PharmaCAP trial): study protocol for a randomized controlled trial - Sunil Shrestha; Ali Qais Blebil; Siew Li Teoh; Simit Sapkota; Bhuvan KC; Vibhu Paudyal; Siew Hua Gan (Taylor & Francis Group, 2023)
Abstract Introduction Evidence-based services to support cancer patients with pain via clinical pharmacy services are currently lacking. Therefore, there is a need to undertake a randomized controlled trial (RCT) to explore the effectiveness of clinical pharmacists (CPs)' input into the multidisciplinary team (MDT) in providing better therapeutic outcomes for cancer pain management. Objectives The main aim of this pilot RCT is to determine the feasibility and preliminary efficacy of integrating CPs into the MDT for cancer pain management on the clinical outcomes of cancer patients experiencing pain. Methods This study protocol outlines two-armed multicenter pilot RCT. Cancer patients suffering from pain will be randomly allocated to receive either clinical pharmacy services, i.e., PharmaCAP trial intervention from the CP, or the usual standard care (i.e., control group). Patients will be recruited consecutively from two hospitals in Kathmandu valley, Nepal. The outcomes will be assessed at baseline (pre-intervention) and 4 weeks post-intervention. The primary feasibility outcomes will include eligibility rate, recruitment rate, willingness to participate, acceptability of screening procedures and random allocation, possible contamination between the groups, intervention fidelity and compliance, treatment satisfaction, and patient understanding of the provided interventions. Subsequently, the primary clinical outcome, i.e., pain intensity of cancer patients, will be assessed. The secondary clinical outcomes will include health-related quality of life (HRQoL), anxiety, depression, adverse drug reactions, and patient medication compliance following the integration of CP into the healthcare team. Discussion The feasibility and potential for integrating CP involvement in MDT to improve clinical outcomes of cancer patients with pain will be evaluated through the PharmaCAP trial. Trial registration: ClinicalTrials.gov NCT05021393. Registered on 25th August 2022.